Gestão e democracia cultural: percepções de trabalhadores e gestores públicos da cultura em​ Varginha-MG - Ramos, Wender Reis (2023)
Culture in the framework of Brazilian public policies, between advances and setbacks, lacks programmatic stability on the part of the public power since the main regulatory milestones of the sector present in the Federal Constitution of 1988 (articles 215 and 216), which, in summary, provide, respectively, the guarantee of the exercise of cultural rights, with encouragement and support for the dissemination of artistic manifestations; and the protection of goods of a material and immaterial nature that constitute the Brazilian cultural heritage. The National System of Culture (SNC), sanctioned in 2010, seeks to materialize these articles. The SNC is the main proposal for the configuration of cultural management in Brazil and, as a structuring model of public management of culture in the country, imposes on the federated entities the organization of their respective culture systems in their own laws, implementing instruments that ensure effective social participation. In the scope of the municipalities, these instruments include the municipal culture fund, the culture conference, the culture council, and the culture plan, all fundamental for the Municipal System of Culture to be configured, as stipulated by the Cooperation Agreements of the Ministry of Culture (MinC). It is precisely in the local context that the necessary arrangements for the development of cultural life are made. The infrastructure for creators, groups and associations to develop their activities, as well as the management of municipal resources for public incentive of cultural activities are under the responsibility of municipal managers. The present research seeks to know how the municipal public management of culture in the city of Varginha (MG), in particular, the managing body of the area, the Cultural Foundation of the Municipality of Varginha (FCMV), approaches the imperative of participation in the cultural sphere and articulates it with the territory of the city. In other words, we analyze cultural management in Varginha to understand how the articulation between the agents of public cultural management and the creators and producers of artistic and cultural expressions takes place in the municipality. To do so, we used two forms of interviews as data collection. In the first, a structured interview with 94 culture workers enrolled in the FCMV public registry, through a virtual questionnaire. In the second, we conducted two group interviews: one with FCMV managers and another with culture workers in Varginha. The non-effectiveness of the Municipal System of Culture of Varginha and the consequent absence of fundamental instruments foreseen in the SNC directly impacts the relationship between workers and public managers of culture in the municipality, since without a plan there are no goals, without goals there is no evaluation, and so on. On the other hand, there is a low engagement on the part of those who demand public management, which favors the disarticulation between these two groups. We also have a mostly informal sector, with people who do not have a professional activity in cultural activities, but rather, a secondary activity. The study exposes a relationship of little dialogue between managers and workers, and it is precisely in relation to the dialogue with the artistic class that FCMV is most demanded. We also noticed a clear disinvestment in the main instrument for financing culture in the municipality, which is the Culture Incentive Law.